2020
DOI: 10.1080/07900627.2020.1755956
|View full text |Cite
|
Sign up to set email alerts
|

Irrigators’ willingness to pay for the adoption of soil moisture monitoring tools in South-Eastern Africa

Abstract: Contingent valuation is used to elicit irrigators' willingness to pay for soil moisture tools in irrigation schemes in Africa, with various econometric methods employed to mitigate potential bias. Key results include that there is a neighbourhood effect influencing adoption, and that being located downstream and spending more on irrigation water positively and statistically significantly influenced willingness to pay for tools. The result suggests that although focusing on economic incentives and promoting far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…In a self-sustaining commercial system, there will be costs in tool manufacture, retailer supply and margins, farmer training and service provision. Abebe et al (2020) found that farmers who experienced access to the soil monitoring tools in the pilot phase would be willing to pay only a portion of the manufacturing cost of the current prototype. Farmers may be willing to purchase soil monitoring tools collectively, depending on the commercial prices, or make a co-payment for subsidized access to tools.…”
Section: Can These Interventions Be Scaled Out and Up?mentioning
confidence: 99%
“…In a self-sustaining commercial system, there will be costs in tool manufacture, retailer supply and margins, farmer training and service provision. Abebe et al (2020) found that farmers who experienced access to the soil monitoring tools in the pilot phase would be willing to pay only a portion of the manufacturing cost of the current prototype. Farmers may be willing to purchase soil monitoring tools collectively, depending on the commercial prices, or make a co-payment for subsidized access to tools.…”
Section: Can These Interventions Be Scaled Out and Up?mentioning
confidence: 99%
“…Low production have mainly been attributed to minimal support by the government to make sure farmers in irrigation schemes get access to inputs and investment loans (BJORNLUND et al, 2017;Rukuni, 1988). Additionally, in south East Africa, for example, ABEBE et al (2020) also reported that most commercial banks have stopped to extend loans to smallholder irrigation schemes, due to collateral issues, this further compromising their infrastructure development projects. They further observed that even though the government has made some efforts to allow micro finance institutions to support smallholder farmers, the uptake for their loans have been minimal due to the fact that their loans have high interest rates, which makes it not viable for most crops smallholder farmers grow in irrigation schemes.…”
Section: Background and Contextmentioning
confidence: 99%
“…There is a research gap in understanding the determinants of crop choices among resource constrained smallholder irrigation farmers who have limited access to markets, finances, management skills and infrastructure (Rattan, 2015). As observed by ABEBE et al (2020), this dimension of enhancing competitiveness in smallholder irrigation schemes has not received direct research attention in the recent past. The immediate benefit of the study is that, based on the information generated, it will give insights into possible viable crop enterprises into smallholder farmers in irrigation schemes can participate while realizing acceptable profit margins.…”
Section: Background and Contextmentioning
confidence: 99%
“…Tensiometers and capacitance sensors that provide information on soil water status are already available [9] but are rarely used in farming systems, particularly at the farm scale, and even more rarely in the Global South. The different barriers to the adoption of precision farming technologies are linked to the user's socio-technical environment, but mostly to (i) economic rationales or (ii) the complexity of using these technologies, including the calibration procedures [10,11].…”
Section: Introductionmentioning
confidence: 99%